2012
DOI: 10.3389/fonc.2012.00113
|View full text |Cite
|
Sign up to set email alerts
|

AZT as a telomerase inhibitor

Abstract: Telomerase is a highly specialized reverse transcriptase (RT) and the maintenance of telomeric length is determined by this specific enzyme. The human holoenzyme telomerase is a ribonucleoprotein composed by a catalytic subunit, hTERT, an RNA component, hTR, and a group of associated proteins. Telomerase is normally expressed in embryonic cells and is repressed during adulthood. The enzyme is reexpressed in around 85% of solid tumors. This observation makes it a potential target for developing drugs that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
(41 reference statements)
1
38
0
Order By: Relevance
“…They are first incubated with AZT (0.8 mM) for 2 weeks. Previously published work suggested that 0.8 mM AZT can induce observable telomere shortening54. Then the genome DNAs are collected and subjected to telomere length measurement.…”
Section: Resultsmentioning
confidence: 99%
“…They are first incubated with AZT (0.8 mM) for 2 weeks. Previously published work suggested that 0.8 mM AZT can induce observable telomere shortening54. Then the genome DNAs are collected and subjected to telomere length measurement.…”
Section: Resultsmentioning
confidence: 99%
“…This effect in cells is related to DNA lesions induced directly by NAs incorporated into genomic DNA, or indirectly by targeting telomerase or ROS-induced oxidative damage. [35][36][37][38][39][40][41][42][43][44][45][46] The phosphorylation occurs soon after DNA damage and accumulates around the break site to attract proteins involved in repair and chromatin remodeling. We found that the level of gH2AX is much greater in both cell lines infected with latent HIV-1, than in un-infected cells, when they were exposed to high concentrations of the NRTI-type of NAs that we tested.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed DDR by exposing cells to high doses of the anti-HIV class of NAs called nucleoside reverse transcriptase inhibitors (NRTIs), choosing AZT (azidothymidine, zivudine) and d4T (stavudine), which are known to incorporate into genomic DNA, affect telomerase and to induce oxidative stress. 36,[38][39][40][41][42][43][44][45][46] The effects of high doses of NRTIs on DNA damage response in latent cells were analyzed by assessing the level of gamma-H2AX (gH2AX), which is a biomarker of DSBs. The gH2AX protein is a histone H2A variant, H2AX, phosphorylated on serine 139 in response to DSBs.…”
Section: Ddr In Latently Infected Cells Responds Less Efficiently To mentioning
confidence: 99%
“…The ultimate result of all these events is cellular genetic instability and DNA damage [11,23]. AZT affects also the growth of cancer cells by inducing telomere shortening [16,25], through inhibition of telomerase reverse transcriptase activity [15,20] and causing cell cycle arrest. The global result is a remarkable antiproliferative effect, leading in some instances to senescence [10,19].…”
mentioning
confidence: 99%